2018
DOI: 10.1002/nag.2867
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical approach to swelling behavior of capillary‐porous media with coupled physics

Abstract: Summary A detailed multiscale analysis is presented of the swelling phenomenon in unsaturated clay‐rich materials in the linear regime through homogenization. Herein, the structural complexity of the material is formulated as a three‐scale, triple porosity medium within which microstructural information is transmitted across the various scales, leading ultimately to an enriched stress‐deformation relation at the macroscopic scale. As a side note, such derived relationship leads to a tensorial stress partitioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The solutions to the boundary value problems in Equations (1) and (2) give the local microscopic fields, including the stress and fluid velocity fields, in terms of the prescribed macrostrain and macropressure gradient. The average stress and velocity in the REV are then obtained as:…”
Section: Homogenization Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The solutions to the boundary value problems in Equations (1) and (2) give the local microscopic fields, including the stress and fluid velocity fields, in terms of the prescribed macrostrain and macropressure gradient. The average stress and velocity in the REV are then obtained as:…”
Section: Homogenization Problemmentioning
confidence: 99%
“…For an oblate spheroid having a very low aspect ration ( ≪ 1), ie, penny-shaped, the Eshelby's tensor, when expanded to the first order in , is as follows: in terms of microcrack aspect ratio = ℎ∕ (2 ). A first-order expansion in is considered, which is valid for aspect ratios ≪ 1.…”
Section: C3 Oblate Spheroidmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that montmorillonite plays an important role in the swelling and shrinking of expansive soil. Starting with nanolevel minerals is a prerequisite to fully understand and clarify its deformation and destruction [11]. However, it is highly difficult to test the interaction between the solid and liquid molecules of crystal layer by experimental methods, which hinders the further development of clay mineralogy to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges apply to model unsaturated soils as a multiscale multiphysics problem. () To formulate a high‐fidelity physics‐based multiscale computational framework for unsaturated soils, we first need to obtain the fundamental physical information at the interfacial scale of such materials.…”
Section: Introductionmentioning
confidence: 99%